Auxin transporters and binding proteins at a glance - Grones, Peter; Friml, Jiří (Journal of cell science, 2015)
The plant hormone auxin is a key regulator of plant growth and development. Differences in auxin distribution within tissues are mediated by the polar auxin transport machinery, and cellular auxin responses occur depending on changes in cellular auxin levels. Multiple receptor systems at the cell surface and in the interior operate to sense and interpret fluctuations in auxin distribution that occur during plant development. Until now, three proteins or protein complexes that can bind auxin have been identified. SCF(TIR1) [a SKP1-cullin-1-F-box complex that contains transport inhibitor response 1 (TIR1) as the F-box protein] and S-phase-kinase-associated protein 2 (SKP2) localize to the nucleus, whereas auxin-binding protein 1 (ABP1), predominantly associates with the endoplasmic reticulum and cell surface. In this Cell Science at a Glance article, we summarize recent discoveries in the field of auxin transport and signaling that have led to the identification of new components of these pathways, as well as their mutual interaction.
Keywords: proteiny huseníčku; Receptors, Cell Surface; F-Box Proteins; Carrier Proteins; Arabidopsis Proteins; F-box proteiny; kyseliny indoloctové; aktivní transport; Indoleacetic Acids; Arabidopsis; transportní proteiny; receptory buněčného povrchu; Biological Transport, Active